2021
DOI: 10.1186/s12936-021-03940-7
|View full text |Cite
|
Sign up to set email alerts
|

The provider’s checklist to improve pregnant women coverage by intermittent preventive malaria treatment in Mali: a pilot implementation study

Abstract: Background Intermittent preventive treatment of malaria in pregnancy (IPTp) is a comprehensive treatment protocol of anti-malarial drugs administered to pregnant women to prevent malaria, started at the fourth pregnancy month, with at least three doses of sulfadoxine–pyrimethamine (SP), taken as directly observed treatment (DOT) every 30 days at intervals until childbirth, in combination with other preventive measures. This paper introduces feasibility and adoption concepts as implementation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…The perception of improving the quality of care for CL management in primary health centres supports HPs’ acceptability of the test and perceptions of its advantages, as seen with malaria RDTs in Ghana and Mali [ 16 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The perception of improving the quality of care for CL management in primary health centres supports HPs’ acceptability of the test and perceptions of its advantages, as seen with malaria RDTs in Ghana and Mali [ 16 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The criteria least applied were "adheres to the quality criteria of the methods involved" of the MMAT; bias controls and description of the type of study in STROBE; while in SRQR were the indication of the research paradigm, characteristics of the research and guarantees of reflexivity, type of study, and techniques to enhance trustworthiness and credibility of the data (Figure 2B). The largest proportion of studies did not indicated the type of mixed study carried out (they only stated the use of quantitative and qualitative techniques); a mixed convergent study was found [43], one explanatory sequential QUAN-Qual [45] and one exploratory QUAN-Qual [44]. Only two studies made explicit the qualitative approach used [29,37].…”
Section: Methodological Quality and Main Topicsmentioning
confidence: 99%
“…The integration of qualitative and quantitative evidence was accomplished in the following ways: the qualitative results were used to create a survey, some findings of the The largest proportion of studies did not indicated the type of mixed study carried out (they only stated the use of quantitative and qualitative techniques); a mixed convergent study was found [43], one explanatory sequential QUAN-Qual [45] and one exploratory QUAN-Qual [44]. Only two studies made explicit the qualitative approach used [29,37].…”
Section: Methodological Quality and Main Topicsmentioning
confidence: 99%
See 2 more Smart Citations